2022
DOI: 10.1186/s12885-022-09535-y
|View full text |Cite
|
Sign up to set email alerts
|

The pathway and characteristics of patients with non-specific symptoms of cancer: a systematic review

Abstract: Background Non-specific symptoms are  common and often sign of a non-serious disease. Because of this, patients with non-specific symptoms of cancer (NSSC) present a challenge for general practitioners (GP). Studies describing characteristics of patients with NSSC have been done after fast-track pathways were created to diagnose and treat patients with NSSC. This study reviews characteristics of patients with NSSC and their patient pathways. Materials and methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…These results were in keeping with the literature, for instance Chapman et al found the three most common cancers to be GI-cancers (upper and lower) (35%), lung (22%), and haematological (13%) 24 . Several other national and international studies found comparable results albeit with variations in numbers 25,26,29,34 .…”
Section: Comparison With Existing Literaturementioning
confidence: 54%
See 1 more Smart Citation
“…These results were in keeping with the literature, for instance Chapman et al found the three most common cancers to be GI-cancers (upper and lower) (35%), lung (22%), and haematological (13%) 24 . Several other national and international studies found comparable results albeit with variations in numbers 25,26,29,34 .…”
Section: Comparison With Existing Literaturementioning
confidence: 54%
“… 24 Several other national and international studies found comparable results, albeit with variations in numbers. 25 , 26 , 29 , 34 …”
Section: Discussionmentioning
confidence: 99%
“…A number of NSSC-CPP studies has previously been conducted in Denmark [ 43 ]. However, these have almost exclusively been based on the early years of the urgent referral programme from 2011 up until the end of 2015 with timeframes usually of 1–3 years [ 24 – 30 , 44 , 45 ], the latter of which limits the possibilities of looking at differences over longer periods of time.…”
Section: Discussionmentioning
confidence: 99%
“…Despite an increase in 5-year survival rates from 15% in the 1970s to 33% in the 2010s, these rates remain relatively Am J Cancer Res 2024;14(1):355-367 low compared to other cancer types [2]. Gastric cancer is often marked by non-specific symptoms, and it often progresses unnoticed due to the delay in onset of clinically detectable symptoms [3]. When the disease is diagnosed at the metastatic stage, the prognosis is generally poor and radical surgery is not indicated [4].…”
Section: Introductionmentioning
confidence: 99%